Electroacupuncture therapy on non-motor symptoms of patients with Parkinson's disease: results of a pilot study. - Chávez-Luévanos, Beatriz; Martínez-Roque, Denisse; Castillo-Torres, Sergio A.; Meléndez-Flores, Jesús D.; Morales-Chapa, Abril T.; Alvarado-Leyva, Laura; Estrada-Bellmann, Ingrid (Revista Mexicana de Neurociencia)
Objective: This study aims to assess the effect of electroacupuncture (EA) on non-motor symptoms in Parkinson's disease (PD) patients as a primary goal and motor symptomatology as a secondary outcome. Methods: Twenty-five patients were enrolled in a non-controlled pilot study that involved a 10-session EA intervention in 16 acupoints, applied 3 times a week for 4 weeks. Motor, non-motor, cognitive, and quality of life evaluation were conducted before intervention and 7 days after concluding the last EA session through MDS-Unified PD rating scale (MDS-UPDRS), Non-motor Symptom Scale (NMSS), montreal cognitive assessment (MoCA), and PD questionnaire (PDQ-8), respectively. Results: Patients showed significantly lower scores in the MDS-UPDRS Part II (7.0 ± 5.7 vs. 10.5 ± 7.6, p = 0.046) and Part III (14.0 ± 8.6 vs. 23.1 ± 13.9, p = 0.002), and NMSS total score (35.2 ± 26.6 vs. 54.6 ± 32.5, p = 0.004) in the post-intervention evaluation, with mood/cognition domain of the NMSS being the only significantly affected by treatment. MoCA total score increased after the intervention (24.2 ± 4.5 vs. 21.6 ± 4.3, p = 0.020), while PDQ-8 scores were not significantly affected by the intervention. Conclusions: Non-motor and motor symptomatology were significantly improved after concluding a 10-session EA therapy. Mood and cognitive disorders were the most positively affected by the intervention. Evaluation of the long-term effects of EA in PD is further needed.